Establishing a non-intubated thoracoscopic surgery programme for bilateral uniportal sympathectomy - Claudio Caviezel; Rolf Schuepbach; Bastian Grande; Isabelle Opitz; Marco Zalunardo; Walter Weder; Sven Hillinger (Swiss Medical Weekly, 2019)
AIM OF THE STUDY